Correlation between serum thyroid hormone and lipid in patients with chronic kidney disease - HUANG Hai-ming; XIAO Xiao-fen; WANG Xiao-qin (Linchuang shenzangbing zazhi)
Objective To study the changes of serum thyroid hormone(TH) and the underlying effects on lipid in patients with chronic kidney disease(CKD) stage3~5.Methods Serum free triiodothyronine(FT3),free thyroxine(FT4),and sensitive thyroid stimulating hormones(s-TSH) concentrations in 120 patients with CKD stage3~5 in hospital and 50 normal-control subjects were measured by a specific radioimmunoassay.Serum total cholesterol(TO,triglycerides(TG),high density lipoprotein(HDL-C),low density lipoprotein(LDL-C),serum creatinine(SCr),blood urea nitrogen(BUN),uric acid(UA),albumin(Alb) concentrationswere measured by a automatic biochemical analyzer,estimated glomerular filtration rate(eGFR) were measured by SCr.Results According to the analysis,serum contents of both FT3 and FT4 were significantly lower in patients with CKD stage3~5than in normal controls(P<0.01,P<0.05,respectively),and their s-TSH contents were not different compared with normal controls(P>0.05).CKD patients had significantly higher serum TG,TC and LDL-C contents than normal controls(P<0.01,P<0.01,P<0.05,respectively),but their HDL-C content is not more different than normal controls(P<0.05).Pearson correlation analysis revels negative correlation betweeen FT3 and TG,TC(r=- 0.288,P<0.05;r=- 0.312,P<0.05),but positive correlation between FT3 and HDL-C,Alb,Hb 0=0.356,P<0.01;r = 0.199,P<0.05;r=0.266,P<0.01;r=0.276,P<0.01).Negative correlation betweeen TC,LDL-C and FT4 were found(r=-0.199,P<0.01;r=- 0.297,P<0.05),and positive correlation between FT4 and eGFR,Alb,Hb(r=0.405,P<0.01;r=0.237,P<0.01;r=0.24,P<0.01),but there is no evidence correlaiton between FT4 and TG,HDL-C,eGFR,TG,TC,HDL-C,LDL-C are not correlated with s-TSH,except Alb.The results of regressive analysis showed that the independent risk factor of hyperlipidemia was eGFR and FT3,that TC was negatively related to eGFR(P<0.01).Conclusions It is very common in middle and advanced stage CKD patients with thyroid dysfunction,which mailnly presents low T3 syndrome and closely related to severity of renal damage.Hyperlipidemia is very common in CKD patients.The risk factors are complicated,which eGFR and FT3 are independent causes of dyslipidemia in CKD patients.